Equity research: Ferrari - allying tradition with innovation - Drumond, João Tomás Silva (2022)
Ferrari is a brand associated with high-performance and elegance, with its cars being status symbols all around the world. However, its sector is facing disruptive times which will challenge the company to modify its ways and processes, becoming more important than ever to understand how the company will tackle these challenges. Therefore, this report focuses on the forecasts of Ferrari’s Net Income and Balance Sheet, taking into account these disruptions, as well as other possible scenarios, and provide a valuation of the company at the end of 2022.